Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Viral Load Kinetics in Symptomatic Children, Adolescents, and Adults. (4th May 2021) - Bellon, Mathilde; Baggio, Stephanie; Jacquerioz Bausch, Frederique; Spechbach, Hervé; Salamun, Julien; Genecand, Camille; Tardin, Aglae; Kaiser, Laurent; L'Huillier, Arnaud G; Eckerle, Isabella
Abstract: SARS-CoV-2 viral load (VL) can serve as a correlate for infectious virus presence and transmission. Viral shedding kinetics over the first week of illness for symptomatic children (n = 279), adolescents (n = 639), and adults (n = 7109) show VLs compatible with infectious virus presence, with slightly lower VL in children than adults.